2020
DOI: 10.1051/0004-6361/202039168
|View full text |Cite
|
Sign up to set email alerts
|

Determining the true mass of radial-velocity exoplanets with Gaia

Abstract: Mass is one of the most important parameters for determining the true nature of an astronomical object. Yet, many published exoplanets lack a measurement of their true mass, in particular those detected as a result of radial-velocity (RV) variations of their host star. For those examples, only the minimum mass, or m sin i, is known, owing to the insensitivity of RVs to the inclination of the detected orbit compared to the plane of the sky. The mass that is given in databases is generally that of an assumed edg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 99 publications
3
49
0
Order By: Relevance
“…For the former, pixels that subtend many arcseconds (as in the case of TESS) can hide stellar companions leading to the inference of erroneous stellar and planetary properties, including radius and density (e.g., Furlan & Howell 2017Ziegler et al 2020). For the latter, the unknown orbital inclination of objects causing long-term accelerations can allow stellar companions to contaminate exoplanet catalogs if an edge-on geometry is assumed (e.g., Kiefer et al 2021). Therefore, direct imaging serves as a practical false-positive checking practice as well.…”
Section: Discussionmentioning
confidence: 99%
“…For the former, pixels that subtend many arcseconds (as in the case of TESS) can hide stellar companions leading to the inference of erroneous stellar and planetary properties, including radius and density (e.g., Furlan & Howell 2017Ziegler et al 2020). For the latter, the unknown orbital inclination of objects causing long-term accelerations can allow stellar companions to contaminate exoplanet catalogs if an edge-on geometry is assumed (e.g., Kiefer et al 2021). Therefore, direct imaging serves as a practical false-positive checking practice as well.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that information from the first Gaia Data Release (DR1) can constrain the mass of RV-detected nontransiting companions (Kiefer et al 2019;Mugrauer & Michel 2020). The GASTON code uses the astrometric excess noise, as published in DR1, to determine the amplitude of the astrometric motion of the host star of a known RV-detected companion (Kiefer 2019;Kiefer et al 2019Kiefer et al , 2021. This measures, or at least constrains from below, the inclination of the orbit, and thus resolves inclination ambiguity on the true mass.…”
Section: Gaia Astrometrymentioning
confidence: 99%
“…Starting from the RV-derived parameters of the companion, the parallax of the star and an estimation of its mass as priors, GASTON uses a MCMC algorithm to explore the space of astrometric orbits compatible with the measured astrometric excess noise, hereafter ε DR1 , and hence to constrain the possible inclinations. It accounts for the systematics in the Gaia DR1 catalog and distinguishes between stars belonging to the TGAS (Tycho-Gaia Astrometric Solution) and the secondary subset of the DR1 catalog (Lindegren et al 2016;Kiefer et al 2021). For the targets in the TGAS dataset, the inputs to the 5-parameter fit include a 24-yr older Tycho-2 or HIPPARCOS-2 astrometric point in addition to 14 months of Gaia measurements, leading to an improved proper motion accuracy.…”
Section: Gaia Astrometrymentioning
confidence: 99%
See 2 more Smart Citations